Phylogenetic analysis of the order Pleuronectiformes (Teleostei) based on sequences of 12S and 16S mitochondrial genes - Azevedo, Marisa F. C. [UNESP]; Oliveira, Claudio [UNESP]; Pardo, Belén G.; Martínez, Paulino; Foresti, Fausto [UNESP] (Sociedade Brasileira de Genética, 2008)
The fish order Pleuronectiformes, composed of 14 families, has two suborders: Psettodoidei (with one family) and Pleuronectoidei (with thirteen families). The relationships among families of Pleuronectoidei and among the genera of their families have extensively been debated and a consensus has not yet been reached. In the present study, partial sequences of the 12S and 16S mitochondrial rRNA genes were obtained from 19 species belonging to the families Achiridae, Bothidae, Cynoglossidae, Paralichthyidae, Pleuronectidae, Scophthalmidae, and Soleidae. Additional sequences of 42 pleuronectiform species were obtained from GenBank. Phylogenetic analyses were conducted by the methods of maximum-parsimony, maximum-likelihood and Bayesian inference. Our results corroborate the monophyletic status of all families, excluding Paralichthyidae. In the family Achiridae, the genus Catathyridium (freshwater) was the sister group of Trinectes (saltwater), and Hypoclinemus (freshwater) was the sister group of Achirus (saltwater). Assuming that the putative ancestor of achirids lived in saltwater, it is suggested that the freshwater habitats in South America were colonized independently by different achirid lineages.
Keywords: phylogeny; molecular systematics; mitochondrial DNA; fish evolution; flatfishes